2000
DOI: 10.1128/iai.68.7.4180-4188.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Putative Proteinase Maturation Protein A of Streptococcus pneumoniae Is a Conserved Surface Protein with Potential To Elicit Protective Immune Responses

Abstract: Surface-exposed proteins often play an important role in the interaction between pathogenic bacteria and their host. We isolated a pool of hydrophobic, surface-associated proteins of Streptococcus pneumoniae. The opsonophagocytic activity of hyperimmune serum raised against this protein fraction was high and species specific. Moreover, the opsonophagocytic activity was independent of the capsular type and chromosomal genotype of the pneumococcus. Since the opsonophagocytic activity is presumed to correlate wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 55 publications
3
49
0
Order By: Relevance
“…In the genome of S. pneumoniae R6, highly conserved copies of the CodY-box were found upstream of genes (putatively) involved in nitrogen metabolism and especially of those concerned with the biosynthesis of BCAAs. Most interestingly, the CodY-box is present upstream of ppmA and rgg, two genes that are known to be involved in virulence of this human pathogen (59,60). In contrast to B. subtilis, a CodY-box is present in the upstream region of S. pneumoniae R6 codY, which suggests that transcription of codY of the latter organism, like that of L. lactis, is auto-regulated.…”
Section: The Cody Promoter Region Contains a Cody-box And Ismentioning
confidence: 87%
“…In the genome of S. pneumoniae R6, highly conserved copies of the CodY-box were found upstream of genes (putatively) involved in nitrogen metabolism and especially of those concerned with the biosynthesis of BCAAs. Most interestingly, the CodY-box is present upstream of ppmA and rgg, two genes that are known to be involved in virulence of this human pathogen (59,60). In contrast to B. subtilis, a CodY-box is present in the upstream region of S. pneumoniae R6 codY, which suggests that transcription of codY of the latter organism, like that of L. lactis, is auto-regulated.…”
Section: The Cody Promoter Region Contains a Cody-box And Ismentioning
confidence: 87%
“…Involvement in virulence has been suggested for PpmA. Overweg et al (2000) demonstrated that mutation of ppmA of strain D39 increased the survival rate of mice. SlrA knockout mutants have been shown to be less efficient in the nasopharyngeal colonization of mice, and this has been attributed to the decreased ability of the knockout mutants to adhere to nonprofessional cells (Hermans et al, 2005).…”
Section: Lipoproteins: Implications In Substrate Transport and Virulencementioning
confidence: 99%
“…Seven of the 16 GAS-specific antibodies were reactive in situ with several GAS antigens demonstrating high levels of immunoreactivity or abundance ( Figure 5; Supplementary 27 a significant note, given that PrtM-immunized mice are protected against S. pneumoniae infection. 46 Despite limited detection of malE RNA transcripts (M5005_Spy1058; ranked 561st); a surprisingly high degree of immunoreactivity was observed for the solute-binding surface lipoprotein Figure 3. Analysis of variance revealed a significant strain effect in the in vivo microarray expression data.…”
Section: Immunohistochemical Analysis Of Mouse Tissuementioning
confidence: 99%